ANALISIS DRAMATURGI PIDATO PRESIDEN SUSILO BAMBANG YUDHOYONO (SBY) TENTANG INSIDEN DI SEPUTAR PERAIRAN PULAU BINTAN1 SEBAGAI PEMENTASAN - Katubi Katubi (Jurnal Masyarakat dan Budaya, 2011)
The incident around Bintan Island on August 13, 2010 between Indonesia-Malaysia resulted in many protests and demonstrations against the Malaysian Government and the Indonesian President, Susilo Bambang Yudhoyono (SBY). SBY was regarded indolent to act. Public also accused the Indonesian Government had something concealed in this incident. It threatened SBY’s reputation, especially to the positive self image he has built. As one of the ways of saving his reputation, President SBY delivered an official speech regarding the Indonesian-Malaysian relationship on September 1, 2010. This article analyzed SBY’s speech using the dramaturgy framework i.e. the elements of settingaudience and language use. On a wider level, it shows that there is a gap on perceived nationalism between the Presiden SBY and furious public.Keywords: SBY’s speech, performance, dramaturgy, nationalism